Evaluating the Impact of Product Diversification on Financial Performance of Selected Nigerian Construction Firms - Nasiru Adamu; Ibrahim Khalil Zubairu; Yahya Makarfi Ibrahim; Aliyu Makarfi Ibrahim (Journal of Construction in Developing Countries, 2011)
The need for the improved performance and continuous survival of construction firms has caused firms to diversify into other businesses. The purpose of this study is to determine the influence of diversification on the performance of some Nigerian construction firms. Financial statements from seventy construction firms were analysed. The specialisation ratio method was used to measure and categorise the firms into undiversified, moderately diversified and highly diversified firms, and profitability ratios were used to measure the group-wise performance of the firms. The Student t-test was used to test the relationship between the extent of diversification and performance. The findings reveal that undiversified firms outperform the highly diversified firms in terms of Return on Total Assets and Profit Margin. Similarly, the moderately diversified firms were found to outperform the highly diversified firms in terms of Return on Equity, Return on Total Assets and Profit Margin. However, no performance difference was found between the undiversified firms and the moderately diversified firms based on the three measures used. A nonlinear relationship was found between the extent of diversification and performance. It was concluded that diversification does not necessarily lead to an improvement in profitability. The implication is that firms are better-off remaining focused if the aim is to improve financial performance.